Analisis Peran Wanita Dalam Hukum Perkawinan di Indonesia Ditinjau dari Perspektif Gender - Susilo Surahman (Jurnal Penelitian Pendidikan, 2014)
This research aims at analyzing the role of women in the marital law viewed from thegender perspective. The role of women in the marital law viewed from a gender perspectiveis intended to achieve a harmonious equal partnership between men and women or genderequality and justice, especially in marriage life. The marital law in Indonesia has placedmen and women in the same position. However, being further investigated, there are stillsome issues that are still affected by gender bias, particularly in terms of the rights andobligations of husband and wife.